A Five-Year Data in Descriptive Study of Systemic and Ocular Risk Factors of Non-arteritic Anterior Ischemic Optic Neuropathy (NAION) and The Correlation to The Clinical Condition - Syntia Nusanti; M. Sidik; Andhika Rachman; Miratasya Zulkarnaen (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Purpose: To acknowledge the demographic, clinical characteristic and the systemic and ocular risk factors in patients with Non-Arteritic Anterior Ischemic Optic Neuropathy (NAION) in 2012-2017 in Cipto Mangunkusumo Hospital. Methods: Retrospective descriptive study using the medical record data of 272 patients with NAION in the past 5 years (2012-2017). Results: In the past 5 years, most of the patient’s initial visit visual acuity was <3/60, most patient had 2-3 systemic risk factors, the most frequent risk factors were hypertension (73.9%), obesity(63.5.%), diabetes mellitus (54.6%), smoking habit (54.5%), dyslipidaemia (46%), hypercoagulable state (19%), history of cardiovascular disease (10.3%) and stroke (7.2%). The risk factors were similar in age range ? 50 or bellow. Based on the initial visit time, most of the patient came to CM hospital in average 15.16 (SD±38.3) weeks. Conclusion: This descriptive study showed classic demographic characteristic of NAION cases. Obesity as the second highest probable risk factor is rarely mention in the other studies. Should future detailed studies be done